Passive smoking: knowledge and awareness of potential risks of passive smoking amongst visitor in Hospital Selayang, Malaysia - Mohd Sufian, Noor Aidafiana; Muhammad Sharif, Najwa Anaqi (2016)
Passive smoking is the inhalation of smoke,called second-hand smoke (SHS), or envviromental tobacco smoke, by persons other than the intended ‘’active” smoker. It occurs when tabacco smoke permeates any enviroment, causing its inhalation by people within that enviroment,Second-hand smoke is a mix of smoke from a lit cigarette, pipe or cigar, plus smoke blown into the air by ‘’active” smoker .The tobacco smokes is poisonous and consist over 4000 chemicals which cause critical disease including cardiovascular disease, lung cancer, respiratory diseases, and also death. One of the chemical is found in the second-hand smoke is are Benzo[a]pyrene or coal tar, one of the most potent cancer-causing chemicals. People who do not smoke and exposed regularly to the toxic chemicals in second-hand smoke can suffer serious and life-threatening health concerns while pregnant women who continously exposed to tobacco smoke can have a greater risk of miscarriages and babies with low birth weight. Therefore, the purpose of this research is to review the level of knowledge and awareness amongst the visitor concerning potential risks of passive smoking. The studies was conducted from November to December 2015. The questionnaire was distributed randomly amongst the visitors and it consists of two main part, which are demographic data of respondents and the respondents awareness and knowledge regarding passive smoking. The data was then tabulated and analyzed using Microsoft Excel and SPSS. Out of 50 respondents who successfully completed the survey, most of them (56%; n= 28) did not aware of the risk faced by the secondhand smoker. Although this study was conducted in small population, it is hoped that the result from this survey will provide some information on how to improve the awareness and knowledge about passive smoking in future.